PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN. 58 BALAI MAKAM KECAMATAN MANDAU - Deni Cutmarita; Lazim N Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. This study was conducted due to the low results of social studies grade IV SDN. 58 Balai Makam. Based on the observation and analysis of the teachers at the beginning of the data class IV SDN. 58 Balai Makam, note that results for students in social studies is very low. Of the 35 students who reached the KKM only as many as 15 people (42.86%), while students who have not completed the study as many as 20 people (57.14%) with an average value of 65.9. This study aims to improve student learning outcomes IPS through Application of cooperative learning model type Numbered Heads Together (NHT). in Class IV SDN.58 Balai Makam Mandau sub Kab. Bengkalis. Based on the results seen an increase in the average student learning outcomes, on average on a base score of 65.9 in the first cycle increased to 78.3 and the second cycle increased again to 86.5. the activities of teachers and students also increased. In the first cycle an average of 79.2% of teacher learning activities with both categories increased to 90.67% of the average activity in the second cycle teachers with very good category. The average activity of students in the first cycle was 75% in both categories, on the second cycle increased to 89.58% with the category very well. Based on analysis of these data it can be concluded that the adoption of the type NHT learning model can improve learning outcomes IPS grade IV SDN. 58 Balai Makam Mandau sub Kab. Bengkalis.Key Words: Learning Outcomes IPS, Model Cooperative Learning type Numbered HeadsTogether (NHT), Evaluation.